2020
DOI: 10.1016/j.jtcvs.2019.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk score for early saphenous vein graft failure: An individual patient data meta-analysis

Abstract: Objectives: Early saphenous vein graft (SVG) occlusion is typically attributed to technical factors. We aimed at exploring clinical, anatomical, and operative factors associated with the risk of early SVG occlusion (within 12 months postsurgery). Methods: Published literature in MEDLINE was searched for studies reporting the incidence of early SVG occlusion. Individual patient data (IPD) on early SVG occlusion were used from the SAFINOUS-CABG Consortium. A derivation (n ¼ 1492 patients) and validation (n ¼ 372… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…The β coefficient (β i ) of each category was determined by multiple logistic regression analysis (Table 3). In order to determine the weight of each category, the age was converted into a categorical variable, and the weight was assigned as the value of average age (22,23). In addition, for the other categorical variables such as gender, race, marital status, tumor stage, histologic grade, surgery, and chemotherapy, the weight of the reference category (W iRef ) was defined as 0 and the weight of the other categories (W ij ) were assigned as 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The β coefficient (β i ) of each category was determined by multiple logistic regression analysis (Table 3). In order to determine the weight of each category, the age was converted into a categorical variable, and the weight was assigned as the value of average age (22,23). In addition, for the other categorical variables such as gender, race, marital status, tumor stage, histologic grade, surgery, and chemotherapy, the weight of the reference category (W iRef ) was defined as 0 and the weight of the other categories (W ij ) were assigned as 1.…”
Section: Discussionmentioning
confidence: 99%
“…the system, we defined B to reflect the decrease of risk when age has increased 10 years ( 22): B = −0.05 × 10 = −0.5. Finally, the score of each category was computed by β i × (W ij -W iRef )/B (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…They found, in a sample of the study group, that EVH was associated with a reduced graft patency (42% vs. 6%) although this was not related to an increase in angina, myocardial infarction or mortality (30). A recent patient-level data meta-analysis using only EVH from experienced centres identified that endoscopic harvest might even reduce the risk of graft failure (31).…”
Section: Evh Graft Patency and Clinical Outcomesmentioning
confidence: 99%
“…Risk factors selection was based on previous studies (10,11,(15)(16)(17)(18) and clinical experience. Factors chosen were those easily measured and recorded.…”
Section: Rationale For Risk Factor Selectionmentioning
confidence: 99%